2020
DOI: 10.1055/s-0040-1708553
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Arrest and Malignant Ventricular Tachycardia in an 8-Year-Old Pediatric Patient Who Has Hemolytic Uremic Syndrome Associated with Shiga Toxin-Producing Escherichia coli

Abstract: Gastrointestinal, neurological, pancreatic, hepatic, and cardiac dysfunction are extrarenal manifestations of hemolytic uremic syndrome associated with Shiga toxin-producing Escherichia coli (STEC-HUS). The most frequent cause of death for STEC-HUS is related to the central nervous system and cardiovascular system. Cardiac-origin deaths are predominantly related to thrombotic microangiopathy-induced ischemia and the immediate development of circulatory collapse. STEC-HUS cardiac related deaths in children are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Arrhythmias and related effects are less common in HUS [ 4 ]. In some case reports, ventricular tachycardia and, although rare, sudden cardiac death have been reported [ 16 ]. Predicting which of the patients diagnosed with HUS may be at risk of cardiac arrhythmia will guide physicians about treatment management during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias and related effects are less common in HUS [ 4 ]. In some case reports, ventricular tachycardia and, although rare, sudden cardiac death have been reported [ 16 ]. Predicting which of the patients diagnosed with HUS may be at risk of cardiac arrhythmia will guide physicians about treatment management during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has suggested that among cardiac manifestations, myocardial dysfunction, TMA in cardiac vasculature, and pericardial effusion leading to pericardial tamponade were the most commonly proposed mechanisms leading to ECMO requirement in these patients. [1][2][3]6,13,14 We found that similar manifestations were more likely to result in the requirement for ECMO in critically ill children with HUS. Early recognition by myocardial enzyme estimation and timely echocardiography may help the clinical team determine the level of cardiac involvement to then help reverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%